Estruturas de copa e raiz de espécies arbóreas do Cerrado nos primeiros anos de crescimento - Silva, Ricardo Rafael Ribeiro da (Universidade Federal de São Carlos, 2016)
Tree species of the cerrado vegetation show several degrees of leaf deciduousness such as the deciduous, semi deciduous and evergreen. However, it is not clear if these groups are functional groups. The main objective of this dissertation was to identify sets of characteristics and their compromises in each leaf phenological group that could identify functional groups since the early years of development. By identifying interrelationships of traits, it was possible to established syndromes that could characterize functional groups. We used canopy and root architecture as well as biomass partitioning as sets of traits to identify functional groups. Deciduous showed a relatively more vigorous root system, reaching greater depths, and higher total biomass of fine roots in relation to semi deciduous and evergreen species. There were more biomass of fine roots occupying the upper layers of soil and thick roots in the deeper layers in deciduous species. Additionally, the architecture of deciduous showed longer branches and higher biomass in heterotrophic portion. The leaf phenological groups were separated significantly into three functional groups. Deciduous and evergreen showed contrasting traits. The semi deciduous species usually occupied the intermediate position. By using sets of traits from roots and canopy it was possible to separate significantly deciduous, semi deciduous e evergreen species into three functional groups where leaf deciduousness was just one of several intertwined characteristics in each group.
Keywords: Cerrado; Grupos funcionais; Espécies arbórea; Copa; Raiz; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA